Using COVID-19 Oral History Archives to Support Equitable and Creative Solutions to Contemporary Public Health Challenges - Emma K. Tsui; Steffie Kinglake; J. Robin Moon; Riki H. S. Eijima; Amy Starecheski (International Journal of Qualitative Methods)
The COVID-19 pandemic sparked what may be the largest number of oral history projects addressing a single public health issue. These collections range from brief informal efforts like those created in classrooms across the country to rigorous and formal projects led by institutions and those with expertise in oral history and archiving. The contribution of this article to existing methodological knowledge is that it brings an underutilized form of qualitative data—namely, COVID-19 oral history archives—into view for public health researchers and practitioners, and provides actionable guidance on using these data to address public health challenges. First, we orient readers to the range of existing COVID-19 archives, the questions they speak to and materials they include, and their current levels of accessibility. Second, we describe three ways that these archives might be used by the public health field to improve trustworthiness, preparedness, and health equity. These paths include: (1) Research: Using archives as a source of in-depth qualitative data on COVID-19 lived experiences to build contextualized understandings and refine ongoing emergency response and preparedness, (2) Teaching: Listening to archives as an opportunity for public health students to center the margins and strengthen emotional intelligence and empathy, and (3) Public Engagement: Creatively activating archives to deepen understanding of different truths and the different mindsets that shape our ability to achieve health equity. We anchor these paths with descriptions of how each might unfold based on existing work and/or models. Through these paths, we argue that oral history archives are a powerful resource for equitably and creatively addressing public health challenges.